Large Genomic Deletions inAIPin Pituitary Adenoma Predisposition - Marianthi Georgitsi; Elina Heliövaara; Ralf Paschke; Ajith Kumar; Marc Tischkowitz; Outi Vierimaa; Pasi Salmela; Timo Sane; Ernesto De Menis; Salvatore Cannavò; Sadi Gündoğdu; Anneke Lucassen; et al. (2008)
Germline mutations in AIP have been recently shown to cause pituitary adenoma predisposition (PAP). Subsequently, many intragenic germline mutations have been reported, both in familial and in sporadic settings.Our objective was to evaluate the possible contribution of large genomic germline AIP deletions, an important mutation type in tumor predisposition syndromes, in PAP.Here, we applied the multiplex ligation-dependent probe amplification assay to examine whether large genomic AIP or MEN1 alterations account for a subset of PAP cases.The study was performed on familial and sporadic pituitary adenoma cases of European origin, which had previously tested negative for germline AIP and MEN1 mutations by sequencing.Two of 21 pituitary adenoma families (9.5%) were found to harbor an AIP deletion. No copy number changes were detected among 67 sporadic pituitary adenoma patients. No MEN1 deletions were found.The present study shows that large genomic AIP deletions account for a subset of PAP. Therefore, in suspected PAP cases undergoing counseling and AIP genetic testing, multiplex ligation-dependent probe amplification could be considered if direct sequencing does not identify a mutation.